Inspección de una losa de 70 años de un edificio en el Golfo de México - Castro-Borges, P.; Balancán-Zapata, M.; López-González, A.; Córdova-Quintal, M. (Revista ALCONPAT, 2014)
The Progreso pier has a head which is a seventy year-old building that is exposed to an aggressive environment in the Gulf of Mexico. As a consequence of the chloride exposure and lack of maintenance, the slabs have shown strong deterioration symptoms. A previous structural inspection suggested a very expensive and non well understood method to repair the slab, which made the authorities to think about demolition in spite of the collateral damage to other elements like columns and beams. Because of the deterioration level, the authors of this paper suggested a second inspection before demolishing and it was performed on selected parts of the slab. The objective of this work is to discuss details and results of this and previous inspection and diagnosis. The new diagnosis indicated the need of demolishing specific parts of the lower concrete cover of the slab and the substitution of the reinforcement by CFRP. Keywords: inspection, repair, chlorides, electrochemical techniques